Advanced macroeconomics - Romer, David (New York ; London : McGraw-Hill Companies, 1996)
Designed for graduate courses in macroeconomics, this text provides a discussion of major issues and competing theories. The presentation of theories is supplemented with examples of relevant empirical work as a way of illustrating how macroeconomic theories can be applied or tested.
Includes bibliographical references (p. 494-522) and indexes.
oif 23/04/15
Loan
Keywords: Macroeconomics